The Order of Terror : the Concentration Camp. - Sofsky, Wolfgang (Princeton University Press, 2001)
During the twelve years from 1933 until 1945, the concentration camp operated as a terror society. In this pioneering book, the renowned German sociologist Wolfgang Sofsky looks at the concentration camp from the inside as a laboratory of cruelty and a system of absolute power built on extreme violence, starvation, "terror labor," and the business-like extermination of human beings. Based on historical documents and the reports of survivors, the book details how the resistance of prisoners was broken down. Arbitrary terror and routine violence destroyed personal identity and social so